2022
DOI: 10.1155/2022/9264555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed microRNAs Associated with Ischemic Stroke by Integrated Bioinformatics Approaches

Abstract: Ischemic stroke (IS) is one of the leading causes of disability and mortality worldwide. This study aims to find the crucial exosomal miRNAs associated with IS by using bioinformatics methods, reveal potential biomarkers for IS, and investigate the association between the identified biomarker and immune cell pattern in the peripheral blood of IS patients. In this study, 3 up-regulated miRNAs (hsa-miR-15b-5p, hsa-miR-184, and hsa-miR-16-5p) miRNAs in the serum exosomes between IS patients and healthy controls f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Jiang et al performed a bioinformatic analysis using the GEO database to explore the association between exosomal miRNA expression and ischemic stroke [78]. They found that three miRNAs, namely hsa-miR-15b-5p, hsa-miR-184, and hsa-miR-16-5p, were highly expressed in the exosomes of patients with ischemic stroke.…”
Section: Exosomal Mirnas As Biomarkers Of Ischemic Strokementioning
confidence: 99%
“…Jiang et al performed a bioinformatic analysis using the GEO database to explore the association between exosomal miRNA expression and ischemic stroke [78]. They found that three miRNAs, namely hsa-miR-15b-5p, hsa-miR-184, and hsa-miR-16-5p, were highly expressed in the exosomes of patients with ischemic stroke.…”
Section: Exosomal Mirnas As Biomarkers Of Ischemic Strokementioning
confidence: 99%